P593 Biologicals and small molecule combotherapies: promising experience in refractory IBD patients. (21st January 2022) - Juillerat, P; Martinho-Grueber, M; Michetti, P
Abstract: Background: It has been hypothesized that combination of two biologics or with a small molecule could "break the ceiling" of the efficacy (~60%) of currently available biological therapies for IBD patients. The best combinations and their safety are, however, unknown. Methods: A chart review of Inselspital, Bern University hospital und Crohn and colitis center Beaulieu Lausanne, of IBD patients on combination therapy have been performed. Data on disease phenotype, previous treatment and efficacy and safety of the new combinations have been collected and studied to help moving forward the use of this armentarium. Results: Among 18 identified IBD patients (39% women, 10 ulcerative colitis, 8 Crohn's disease) with extended and refractiry luminal disease (indication) who received 21 combination therapies between June 2017 and November 2021. They suffered from steroid-dependency and half of them were refractory to at least two anti-TNF alpha agents. These treatments have been started after a median duration of disease of 6 years (range 1–25) for a mean period of combo treatment of 11 months (range 1–52), 8 were still ongoing. Various combotherapies and clinical response (arrows; red=bad, green=good response) are presented in Figure 1. A partial or complete response was observed in 15/21 therapies (71%) with a mean decrease of CRP of 11 mg/l (range+23 to -59) and calprotectin of 399 mcg/g (range 0 – 1745) among the reponders. Concerning safety, 2 infections (otitis media, skin mycosis), 1 non hodgkin Lymphoma and 4 minor adverse events (tumefaction left parotide, eczema, 2x lymphopenia) have been reported, mostly when small molecules have been involved. Conclusion: Ustekinumab combined with anti-TNF agents in Crohn's disease is more effective than vedolizumab and tofactinib in ulcerative colitis. Combining with small molecules increases the risk of lymphopenia, of cancer (1 case of non hodgkin lymphoma) and minor infections in severe refractory and steroid-dependent inflammatory bowel disease patients.